Analisis Partisipasi Masyarakat Dalam Pelaksanaan Pembangunan Desa Untuk Mengoptimalkan Kesejahteraan Masyarakat Di Desa Bandar Klippa, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - maringan panjaitan; Evi Phaninora Pandiangan (Jurnal Ilmu Sosial Dan Politik, 2022)
The role of participation in the implementation of village development is a very important component for the success of the village development program. So that community participation can run optimally. Therefore, the village government should play an active role in developing community participation in the implementation of development programs. The purpose of this study is to find out how community participation in the implementation of village development is to optimize community welfare. This study uses a qualitative descriptive research method using interview and observation techniques. This study uses "key informants, main informants and additional informants". The result shows that the process of community participation in the implementation of village development is quite good, starting from decision making, implementation of development and evaluation of development. Where the community already has the responsibility in village development, participates in the implementation and participates in the evaluation of development. But there are factors that hinder the process of community participation in the implementation of village development, namely the village government does not have the ability to explain to the community what development will be carried out so that people do not understand and do not understand which results in people not wanting to participate in village development. The conclusion from the results of this study is that community participation in the implementation of village development in Bandar Klippa Village is quite good, as can be seen from the enthusiasm of the community in implementing village development.